2017
DOI: 10.1093/nar/gkx267
|View full text |Cite
|
Sign up to set email alerts
|

A high quality Arabidopsis transcriptome for accurate transcript-level analysis of alternative splicing

Abstract: Alternative splicing generates multiple transcript and protein isoforms from the same gene and thus is important in gene expression regulation. To date, RNA-sequencing (RNA-seq) is the standard method for quantifying changes in alternative splicing on a genome-wide scale. Understanding the current limitations of RNA-seq is crucial for reliable analysis and the lack of high quality, comprehensive transcriptomes for most species, including model organisms such as Arabidopsis, is a major constraint in accurate qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
310
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(330 citation statements)
references
References 73 publications
12
310
1
Order By: Relevance
“…Gene and transcript models for PTB1 , PTB2 , U2AF65A , and SUA reported in AtRTD2 (Zhang et al, ) are shown in Figure S2. The functional and the main non‐functional premature termination codon‐containing (PTC + ) PTB transcripts are referred to as fully spliced (FS) and alternative exon (AE), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Gene and transcript models for PTB1 , PTB2 , U2AF65A , and SUA reported in AtRTD2 (Zhang et al, ) are shown in Figure S2. The functional and the main non‐functional premature termination codon‐containing (PTC + ) PTB transcripts are referred to as fully spliced (FS) and alternative exon (AE), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These were generated with the Flux simulator (Griebel et al, 2012), which takes as input the number of RNA molecules (molecule count) to simulate for each isoform, and can simulate single-or paired-end reads of different lengths. A compendium of 100 simulated samples was generated, containing molecule counts for all isoforms in the AtRTD2-QUASI A. thaliana reference transcriptome (Zhang et al, 2017b). AtRTD2-QUASI is a modified version of AtRTD2 that has been optimized for isoform expression quantification.…”
Section: Resultsmentioning
confidence: 99%
“…In November 2010, the TAIR10 annotation contained 27 416 protein coding genes, of which 21% had more than one known isoform (on average 2.37 isoforms per gene; Lamesch et al, 2012). In 2016, two new annotations were released: Araport11 in which 41% of 27 655 protein-coding genes had more than one isoform with on average 2.94 isoforms per gene (Cheng et al, 2017); and AtRTD2 in which 49% of 27 667 protein-coding genes (60% of 22 453 introncontaining) had more than one isoform with on average 4.44 isoforms per gene (Zhang et al, 2017b). However, the large number of isoforms per gene in AtRTD2 potentially complicates expression quantification as an increased number of isoforms negatively impacts quantification accuracy (Hayer et al, 2015;Kanitz et al, 2015;Zhang et al, 2017a).…”
Section: The Number Of Isoforms Per Gene and Their Physical Overlap Amentioning
confidence: 99%
See 1 more Smart Citation
“…Short‐read sequencing technologies, in conjunction with annotated reference genomes, can be readily applied to a variety of biological questions, including detection (Zhang et al ., ) and analysis of gene expression (Ezer et al ., ), DNA methylation (Zhong et al ., ), identification of transcription factor binding sites and the detection of causal regions and mutations in mutant screens (James et al ., ; Klap et al ., ) or populations (Thoen et al ., ). However, the importance of next‐generation sequencing beyond the context of a single reference accession has long been recognized (Varshney et al ., ).…”
Section: Introductionmentioning
confidence: 99%